Peranan Poliembrioni Terhadap Produksi Benih Pada Tanaman Jeruk Siam (Citrus nobilis L.) - Piri, David Gilbert Young; Raintung, Jeane S.M.; Walingkas, Stanley A.F. (Sam Ratulangi University, 2023)
This study aims to determine the growth of polyembryonic seeds in Siamese oranges and to study the growth of seedlings from polyembryonic seeds which will be used as good seeds in overcoming the problem of availability of Siamese orange seeds. The research was carried out from May to October 2022 at the Green House of the Faculty of Agriculture, Sam Ratulangi University and Eris Village, Eris District. The research method used a randomized block design (RBD) with 5 treatments repeated 4 times and found a total of 20 treatments, namely Z11, Z12, Z13, Z14, P21, P22, P23, P24, P31, P32, P33, P34, B21, B22, B23 , B24, B31, B32, B33 and B34. Data analysis used ANOVA analysis (analysis of variance). If it has no effect, then proceed with the BNT test at the 5% test level. The results showed that the growth of Siamese orange sprouts resulted in the growth of embryos up to 6 intact in one seed. Polyembryony, the ability to germinate seeds above 80.00% is one of the conditions for seeds to be recommended for seed sources 20.95%.